Perencanaan Kawasan Prioritas Penyediaan Air Bersih menggunakan Fuzzy Multi Criteria Decision Making - Winata, Angger Setia; Suswaini, Eka; Ritha, Nola (Jurnal Sustainable: Jurnal Hasil Penelitian dan Industri Terapan, 2018)
The Provision of water for the community, there are some problems and until now can not be overcome completely. Especially in slum areas that are prone to water so that people have difficulty to get water. Many of slums in Kab. Lingga becomes a separate problem for the planning of water supply, from the problem it is designed a system that aims to determine the priority area of water supply by implementation the fuzzy multi criteria decision making method in the planning of the priority area of water supply, obtaining the region with the highest total integral value that is Marok Tua with a value of Î±0 is 0,34375, Î±0,5 is 0,51875, Î±1 is 0,69375.